Have We Left the Boys Behind? Addressing the Decline of Male Participation in Higher Education in Quebec - Papi, Cathia; Thériault, Dominic (Médiations & médiatisations, 2025)
Generally, research related to equity, diversity, and inclusion (EDI) focuses on people with disabilities, ethnic or cultural minorities, and sexual or gender minorities. It follows in the tradition of initiatives that have progressively enabled women to take their place in society, expanding these efforts to include a broader range of underrepresented groups. Men who do not live with disabilities and who are not part of a minority group are therefore often overlooked in these studies. Yet, available data show that in higher education, they have not been the majority among students for quite some time. This highlights the need to examine what is happening earlier in the educational pathway, as academic delays and dropouts often begin in childhood. This invites us to question the potential role that certain technologies could play in supporting boys’ academic success. Additionally, we will see that income inequalities disadvantaging women may also help explain differences in the return on investment in higher education between men and women—underscoring the importance of considering the relationships between traditionally studied minority groups and others who may not appear marginalized at first glance.